Enhanced Water Quality Monitoring for Produced Water Disposal using Cross-flow Membrane Filtration - Khor, E.H.; Samyudia, Y (Department of Irrigation and Drainage, Ministry of Natural Resources and Environment Malaysia., 2013)
The accuracy of oil-in-water analysis for produced water is increasingly crucial as the regulations for disposal of this water are getting more stringent world –wide. According to OSPAR commission, the main component of oil and grease that are being monitored in produced water is the dispersed oil. Therefore, membrane filtration can be incorporated as part of water quality monitoring for the disposal of produced water by separating dispersed and dissolved oil so that the accuracy of measuring the dispersed oil can be enhanced. In this paper, Microfiltration and Ultrafiltration with different material and pore sizes are run at different operating pressures to investigate its effectiveness in maximising the dissolved oil in the permeate. After membrane filtration treatment, samples are analyzed with Gas Chromatography Mass Spectrophotometer (GCMS) to determine the oil content. The concentration of feed, retentate, and permeate obtained from GCMS determines the degree of dispersed and dissolved oil separation. From the study, with comparison to ultrafiltration, microfiltration of pore size 0.2µm Hydrosart® membrane can achieve a more efficient separation of dissolved and dispersed oil in permeate and retentate respectively.